2018
DOI: 10.1140/epjc/s10052-018-5973-z
|View full text |Cite
|
Sign up to set email alerts
|

Complexity factor for static anisotropic self-gravitating source in f(R) gravity

Abstract: In a recent paper, Herrera (Phys Rev D 97: 044010, 2018) have proposed a new definition of complexity for static self-gravitating fluid in general relativity. In the present article, we implement this definition of complexity for static self-gravitating fluid to case of f (R) gravity. Here, we found that in the frame of f (R) gravity the definition of complexity proposed by Herrera, entirely based on the quantity known as complexity factor which appears in the orthogonal splitting of the curvature tensor. It… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Next, following the discussion in section V the constant parameters, namely A, B and C defining the interior solution can be obtained from Eqs. (50) and (64) leading to…”
Section: Stellar Interior: Tolman IV Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, following the discussion in section V the constant parameters, namely A, B and C defining the interior solution can be obtained from Eqs. (50) and (64) leading to…”
Section: Stellar Interior: Tolman IV Modelmentioning
confidence: 99%
“…As before, the parameters A, B and C are obtained from the junction conditions. However, the imposition of constraint (78) slightly changes the information obtained from condition (50). Now from (50) one gets an expression for constant C in terms of the radius R, the constant A, and the free parameters α and λ.…”
Section: B θ-Effects: Mimicking the Density For Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…In [31], Y T F was chosen as the complexity factor of the static sphere because it incorporated the essential features of the system and determined their effects on Tolman mass (or active gravitational mass). Equation (34) indicates that Y T F contains the contribution of the significant factors which induce complexity in the current setup. Therefore, we proceed by assuming that the scalar Y T F is the best fit for the complexity factor.…”
Section: Complexity and Evolution Of The Systemmentioning
confidence: 99%
“…Recently, the complexity of different geometries has also been explored by employing Herrera's definition and it was shown that complexity of the self-gravitating structures increases in the presence of a massive scalar field [31][32][33]. The concept of complexity has been analyzed in other modified theories as well [34] In this paper, we derive the complexity factor for a dynamical dissipative sphere by considering its pattern of evolution in the background of SBD theory. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%